Perceptions on curriculum implementation: a case for rural Zimbabwean early childhood development teachers as agents of change - Madondo, Fortunate (Taylor and Francis, 2021)
This article examined perceptions on curriculum implementation regarding rural Zimbabwean early childhood development (ECD) teachers in 2017. The study aimed to locate teachers as agents of change in schools by reviewing their perceptions in implementing the recently introduced ECD framework. In this qualitative multiple case study, 30 rural teachers from Zimbabwe’s 10 provinces shared their views as well as strengths and weaknesses of the competence-based curriculum. Implicit in the teachers’ descriptions of effective curriculum implementation were their perspectives on effective classroom instruction. Such perspectives offer much insight into challenges experienced in curriculum implementation for rural schools. Using teacher agency as a theoretical framework, findings of the study revealed that teachers lack support regarding proper infrastructural facilities, and schools lack human, financial, and material resources for successful curriculum implementation. The researcher recommends that as a basis for future policy, the concerns of teachers, parents, and learners in complex ECD settings need to be highly prioritized by the curriculum makers ahead of planning and implementing a new curriculum.